Effects of Nitrogen Management on Garlic Yield, Economic Benefit and Soil Apparent Nutrient Balance - Bo, Luji; Zhang, Yingpeng; Li, Yan; Luo, Jiafa; Sun, Ming; Zhong, Ziwen; Jing, Yongping (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
An experiment was conducted on garlic (Allium sativum L.) to investigate the effects of nitrogen management on yield, economic benefit and the soil apparent nutrient balance, in the region of Laiwu town in Shandong province, China. The treatments included control (no N fertilizer), urea at 300 kg/ha, urea at 240 kg/ha, combined urea and commercial organic fertilizers at 120 kg N /ha each, and controlled-release nitrogen fertilizer at 192 kg N /ha. Results showed no significant difference both for garlic bulb yield and economic benefits between the urea treatments at different N application rates. The effect of the combined use of urea and organic fertilizer was similar to that of the urea application at the same N application rate. However, garlic bulb yields in the treatment of controlled-release nitrogen fertilizer were significantly higher than in the other fertilizer treatments, even the N application rate was lower. The net income from garlic in the treatment of controlled release fertilizer was also significantly higher than those in the other treatments. There was N surplus after the garlic growth season when urea was applied at 300 kg/ha, while there was N, P and K deficit when the controlled-release N fertilizer at 192 kg/ha was used to produce more garlic. It is suggested that use of controlled release N fertilizer combined with a supplement of other nutrients would be a sustainable strategy for fertilizer management in garlic production.